Implementation of Music Media to Increase Optimism in Lorenza FC Football Players - Fazan Nur Wahid; Gatot Jariono (UNIB Press, 2022)
Many efforts are used by increasing the optimism of football athletes. However, there are still few research results that examine to increase optimism in football players by implementing music in their activities. Therefore, this study aims to analyze the presence or absence of the influence of music implementation on increasing the sense of optimism of football players. This study is a quantified study with pretest posttest control group design experimental techniques to analyze the presence or absence of the influence of music implementation on increasing the sense of optimism of football players in groups that are implemented music or not. The study involved 22 randomly selected athletes from one of the football groups in Boyolali. which is divided into two groups that represent each of those approaches. The results of the pre-test and post-test are quantitatively analyzed through statistical prerequisite tests, and hypothesis tests using the T-test. From the results of the analysis, it was found that there was a significant influence in the implementation of music media on increasing the sense of optimism of football athletes which was indicated by an increase in average optimism of 25.83% which experienced an increase in optimism with an average of 14.63%.